2014
DOI: 10.1136/oemed-2014-102362.253
|View full text |Cite
|
Sign up to set email alerts
|

0170 Shift work and hypertension: prevalence and analysis of disease pathways in German car manufacturing workers

Abstract: Method We completed searches of MEDLINE and PSYCInfo from inception of each database to June 2013, to identify primary studies evaluating symptom exaggeration among patients with mental health disorders. Teams of reviewers completed title and abstract screening of citations, full text review of potentially eligible articles, data extraction, and quality assessment of eligible studies. Findings from our review and input from content experts informed the development of a summary instrument. Results We identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Moreover, they build upon an existing body of epidemiological studies showing associations between shift-work and the incidence and prevalence of these factors in working age adults (Barbadoro, Santarelli et al, 2013; Karlsson, Knutsson et al, 2001; Kim, Son et al, 2013; Kirsh, Cotterchio et al, 2014; Knutsson & Kempe, 2014; Lieu, Curhan et al, 2012; Monk & Buysse, 2013; Niedhammer, Lert et al, 1996; Ohira, Tanigawa et al, 2000; Ohlander, Keskin et al, 2014; Oishi, Suwazono et al, 2005; Pan, Schernhammer et al, 2011; van Amelsvoort, Schouten et al, 1999; Yamasaki, Schwartz et al, 1998). Our results extend these previous findings in several respects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, they build upon an existing body of epidemiological studies showing associations between shift-work and the incidence and prevalence of these factors in working age adults (Barbadoro, Santarelli et al, 2013; Karlsson, Knutsson et al, 2001; Kim, Son et al, 2013; Kirsh, Cotterchio et al, 2014; Knutsson & Kempe, 2014; Lieu, Curhan et al, 2012; Monk & Buysse, 2013; Niedhammer, Lert et al, 1996; Ohira, Tanigawa et al, 2000; Ohlander, Keskin et al, 2014; Oishi, Suwazono et al, 2005; Pan, Schernhammer et al, 2011; van Amelsvoort, Schouten et al, 1999; Yamasaki, Schwartz et al, 1998). Our results extend these previous findings in several respects.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments in model organisms and in humans suggest potential links between irregular circadian rhythms and a number of key risk factors for cardiovascular disease including hypertension, obesity, diabetes, and dyslipidemia – the “metabolic syndrome” (Buxton, Cain et al, 2012; Karatsoreos, Bhagat et al, 2011; Leproult, Holmback et al, 2014; Scheer, Hilton et al, 2009; Shi, Ansari et al, 2013; Turek, Joshu et al, 2005). Moreover, several epidemiological studies have demonstrated an association between self-reported shift-work and components of the metabolic syndrome (Barbadoro, Santarelli et al, 2013; Karlsson, Knutsson et al, 2001; Kim, Son et al, 2013; Kirsh, Cotterchio et al, 2014; Knutsson & Kempe, 2014; Lieu, Curhan et al, 2012; Monk & Buysse, 2013; Niedhammer, Lert et al, 1996; Ohira, Tanigawa et al, 2000; Ohlander, Keskin et al, 2014; Oishi, Suwazono et al, 2005; Pan, Schernhammer et al, 2011; van Amelsvoort, Schouten et al, 1999; Yamasaki, Schwartz et al, 1998). …”
Section: Introductionmentioning
confidence: 99%
“…Shift work that causes circadian disruption is associated with increased risk for a number of diseases in humans including cancer and cardiovascular disease [24-28] . In an effort to study the phenomenon of increased inflammation, increased hypertension, and increased CVD risk due to shift work, a recent randomized crossover study was carried out by Morris et al [29].…”
Section: Circadian Blood Pressure Disorders In Humansmentioning
confidence: 99%
“…In a study looking at over 25,000 German car manufacturers 16-64 years old, Ohlander et al concluded that hypertension was lowest among people who did not work in shifts and highest in those who did not work night shifts. 80 After the authors adjusted for behavioral factors, they report no increased risk of hypertension for any shift work category. A Finnish study looked at over 20,000 pairs of twins (the Finnish Twin Cohort) and found no correlation between shift work and increased risk of CVD or hypertension.…”
Section: Shift Workersmentioning
confidence: 99%